Comparison of Instagram Hashtags in Increasing Audience Engagement Through Music Concerts in Indonesia - Paramita, Sinta; Aulia, Sisca; Rusdi, Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
In 2023, various music concerts will begin to be held nationally and internationally. Indonesian music fans came in droves to enliven the music concert. Audience music concert activities do not only focus on concerts and purchasing concert tickets but also on crowds in the virtual sector. The activity of watching a music concert is documented and uploaded via social media and Instagram. The use of hashtags is used to support the concert as well as being a means of self-actualization as a music fan. Uploads on Instagram social media with the hashtag immediately received attention from other social media users who were interested in the concert. From this explanation, this research will look at two things. Firstly, how influential hashtags on Instagram are in increasing audience engagement through three music concerts held in Indonesia. Second, look at the comparison of the three music concert hashtags. The research approach used in this research is quantitative, using extensive data-based social network analysis (SNA) methods. The application used in this research is Analisia.io, an artificial intelligence (AI) social analytic application as a tool for collecting virtual data according to the researchers' criteria. The first result of this research is that #blackpinkworldtourjakarta's cumulative total audience engagement is 17,653. #the90festival cumulative total audience engagement 144,150. And #coldplayjakarta, the total audience engagement was 811,387. The first Instagram hashtag most discussed virally is #coldplayjakarta, the second is the hashtag #the90festival, and the last is the hashtag #blackpinkworldtourjakarta. From this analysis, Instagram hashtag comparison activities in increasing audience engagement through music concerts in Indonesia fall into the concept of a network society: timelessness, the cultural consequences of information capitalism, the power of identity, and changing times.